24 photographs of Poland (London : M.I. Kolin, 1935)
Postcard photographs of Poland, 1935(?). Includes views of 17th century houses; castles; churches; town halls; ports; people in regional costume and some landscapes.
(from postcard captions) Chorzow: a steel foundry -- Czestochowa: the monastery -- Gdynia: A view of the port -- Kazimerz (Central Poland): 17th century houses -- Krakow: The Wawel Castle -- Krakow: Our Lady's Church -- Krakow: the River Vistula -- Lowicz: a procession -- Lwow: the market place -- Mir (Eastern Poland): the castle -- Poland: a peasant woman at a fair -- Poznan: the town hall -- Southern Poland: a country church -- Southern Poland: a view in winter -- Southern Poland: a prcoession -- Suwalki: the "Wigry" Lake -- The Tatra: Mount Koscielec -- Warszawa: St. Alexander's Church -- Warszawa: the Carmelite Church -- Warszawa: The Belvedere Palace -- Warszawa: the old town market place -- Warszawa: the Lazienki Palace -- Wilno: the "Ostra Brama," one of the shrines of Poland.
Title from printed envelope containing set of postcards.
Some of the postcards have statement: Copyright by D.F. Brown.
LC copy imperfect: 1 postcard wanting.
Source unknown.
Printed envelope has ink stamp: "Fundusz Kultury Narodowej".
Keywords: Cities & towns -- Poland; Photomechanical prints -- 1930-1940.; Postcards -- 1930-1940.